The influence of zeolite type in composite cobalt catalyst on the Fischer–Tropsch synthesis product composition - E. V. Kriventceva; K. O. Gryaznov; E. Yu. Khat’kova; L. V. Sineva; V. Z. Mordkovich (Тонкие химические технологии, 2013)
The dependence of zeolite type in a composite catalyst, namely structural features, presence of alkali metal cation and total acidity, on the composition of Fischer-Tropsch product has been shown in the article. Highly dispersed skeleton cobalt (Raney cobalt) was used as active metal. It was found that the presence of zeolite in Hform in the composition of the catalyst results in the formation of a larger number of unsaturated and branched hydrocarbons. The cobalt composite catalyst based on HBeta zeolite is more active and more productive in the synthesis of C5+ hydrocarbons from CO and H2 than the catalyst based on KA zeolite. Assumptions of the role of zeolite acid sites in secondary transformations of hydrocarbons produced from CO and H2 on skeleton cobalt were done.